Changes in field dose–response curves for demethylation inhibitor (DMI) and quinone outside inhibitor (QoI) fungicides against Zymoseptoria tritici, related to laboratory sensitivity phenotyping and genotyping assays. Issue 2 (24th October 2017) - Blake, Jonathan J; Gosling, Paul; Fraaije, Bart A; Burnett, Fiona J; Knight, Stuart M; Kildea, Steven; Paveley, Neil D
Abstract: BACKGROUND: Insensitivity of Zymoseptoria tritici to demethylation inhibitor (DMI) and quinone outside inhibitor (QoI) fungicides has been widely reported from laboratory studies, but the relationships between laboratory sensitivity phenotype or target site genotype and field efficacy remain uncertain. This article reports field experiments quantifying dose–response curves, and investigates the relationships between field performance and in vitro half maximal effective concentration (EC50 ) values for DMIs, and the frequency of the G143A substitution conferring QoI resistance. RESULTS: Data were analysed from 83 field experiments over 21 years. Response curves were fitted, expressed as percentage control, rising towards an asymptote with increasing dose. Decline in DMI efficacy over years was associated with a decrease in the asymptote, and reduced curvature. Field ED50 values were positively related to in vitro EC50 values for isolates of Z. tritici collected over a 14‐year period. Loss of QoI efficacy was expressed through a change in asymptote. Increasing frequency of G143A was associated with changes in field dose–response asymptotes. CONCLUSION: New resistant strains are often detected by resistance monitoring and laboratory phenotyped/genotyped before changes in field performance are detected. The relationships demonstrated here between laboratory tests and field performance could aid translation between laboratory and field for other fungicide groups. © 2017 Society of Chemical Industry Abstract : Over two decades, fungicide efficacy was measured by field experiments and laboratory assays. Significant relationships were identified between decline in field performance and in vitro sensitivity/target site genotype frequency.